Using gene expression to identify the most suitable environmental conditions for growth and metabolism of juvenile deepwater redfish (Sebastes mentella) in the Estuary and the Gulf of St. Lawrence. (11th January 2022) - Martínez-Silva, Maria Angelica; Vagner, Marie; Senay, Caroline; Audet, Céline
Abstract: Deepwater redfish Sebastes mentella will be among the most important resource-sustaining commercial bottom-fish fisheries in the years to come in the Estuary and Gulf of St. Lawrence (EGSL). In 2011, 2012, and 2013, three strong cohorts were recruited to the stock; their abundance in 2018 was 80 times higher than that of the 1993–2012 period. The main goal of this work was to deepen our knowledge of their growth regulation and metabolism in order to identify molecular indicators and determine how they are influenced by natural environmental conditions. Fish weight and water temperature explained 11% of the variation in relative mRNA levels of specific gene targets in liver and muscle among seven sites where deepwater redfish were captured in the EGSL. The relative expression of liver insulin-like growth factor-1 ( igf-1 ) and white muscle A-chain lactate dehydrogenase ( ldh-a ) correlate positively with weight, whereas heavy chain muscle myosin ( myo ), heart citrate synthase ( cs ), and white muscle pyruvate kinase ( pk ) correlate negatively. The relative expression of heart cytochrome c oxidase subunit 1 ( cox-1 ) and white muscle igf-1 receptor isoform a ( igf-1ra ) correlate negatively with temperature. Deepwater redfish from the estuary were smaller than those caught at other sites. Since the growth potential of deepwater redfish was strongly correlated with temperature (being enhanced by higher temperatures), this study suggests an ecological advantage for this species in a climate-warming context.